The impact of gender stereotypes on physical education lessons: a pilot study regarding the qualitative analysis of teachers’ perceptions - Pautu, Anamaria; Petracovschi, Simona; Domokos, Martin (Frontiers in Psychology, 2025)
IntroductionThis study examines the feelings of physical education teachers toward gender stereotypes and their impact on how boys and girls are perceived and supported during physical education classes. It explores how teachers’ expectations and attitudes reflect cultural biases, such as associating boys with physically demanding sports and girls with activities emphasizing grace and flexibility.MethodsSemi-structured interviews were conducted with eight teachers from diverse age groups and work environments (urban and rural). The research utilized MAXQDA software to analyze the emotional tone of the responses, categorizing them as positive, neutral, or negative.ResultsThe findings reveal that teachers generally maintain a neutral tone when discussing gender differences, focusing on objective observations rather than emotional evaluations. However, instances of positive attitudes, such as appreciating girls’ discipline and performance, suggest efforts to challenge stereotypes. In contrast, some responses reflect stricter expectations or criticisms of girls, which can perpetuate negative stereotypes.ConclusionTeachers’ feelings significantly influence how they address gender stereotypes in physical education. Positive sentiments are associated with encouragement and inclusivity, while neutral or negative attitudes often reinforce traditional expectations, allowing stereotypes to persist. These findings underscore the need for targeted training programs to help teachers develop equitable and inclusive practices that reduce the influence of gender stereo-types on students’ experiences in physical education.